Energy Monitoring System Berbasis Web - Zulkarnain, Novan (Bina Nusantara University, 2013)
Government through the Ministry of Energy and Mineral Resources (ESDM) encourages the energy savings at whole buildings in Indonesia. Energy Monitoring System (EMS) is a web-based solution to monitor energy usage in a building. The research methods used are the analysis, prototype design and testing. EMSconsists of hardware which consists of electrical sensors, temperature-humidity sensor, and a computer. Data on EMS are designed using Modbus protocol, stored in MySQL database application, and displayed on charts through Dashboard on LED TV using PHP programming.